Sanksi Pidana Pertambangan Pasir Tanpa Izin (Studi Putusan Nomor 120/Pid.Sus/2017/PN Gin) - I Nyoman Sri Agus Rusnama; Ida Ayu Putu Widiati; I Nyoman Gede Sugiartha (Jurnal Analogi Hukum, 2019)
Often the community ignores making mining permits so that they have a serious impact on the environmental damage around the place that is turned into mining, so the people who conduct mining without a permit are illegal mining. This research, there is the problem of how the application of criminal sanctions against the suspect of the mining of sand without a licence and how the analysis of consideration of judges in meting out the verdict against suspect of sand mining without permission. This type of research used in writing this research is normative legal research . The results of this research concluded bring sanctions against the suspect of the application of sanction/mining without permission Number 120/Pid.Sus/2017PN. Gin criminal punishment with imprisonment for 6 months and a fine of Rp. 1.000.000,-(one million rupiah) but the punishment does not need to be traveled was superseded by a criminal trial for 9 months. Analysis of the judge's consideration in dropping the verdict against suspect of sand mining without permission with the study's verdict number 120/Pid. Sus/2017/PN. Gin that Tribunal judges have been sentencing trial mejatuhkan for 9 months against the defendant the Tribunal Justices see no damning thing and just see things easing, the defendant first time doing criminal, be polite in the trial, and judge argued the law not only retaliation but aims to improve and educate the defendant in order to become better human beings again.